EFFICIENCY OF USING INFORMATION TECHNOLOGIES IN PRIMARY SCHOOLS (Proceedings of International Educators Conference, 2023)
This article discusses information technology, the importance of information technology in improving the effectiveness of education and the order of use of modern information technology in primary school students.